Genetic Polymorphism of IL-4 Gene as Risk Factors for Patients Suffering from House Dust and Storage Mites Allergy - Suaad Almas. Brakhas (Journal of Global Pharma Technology, 2018)
The study was design to show and shed light on the Association between IL-4 Gene polymorphism with allergic Rhinitis and Asthma in patient suffering from House Dust and Storage Mite allergy that diagnosed by Skin Prick test forHouse Dust Mites (HDM) Dermatophagoidespteronys sinus, (D.p), Dermatophagoides farina (D.f) and Intradermal skin test for Storage mites Glycyphagusdomesticus with detected of IL-4 level in serum by ELISA, IL-4 Gene polymorphism (RFLP-PCR), and Total IgE level. A highly significant difference in IL-4 level and totaling E level between allergic asthma, allergic rhinitis and control. In HDM allergy The C allele showed a significant increased polymorphism in Asthma patients (43.33%) and rhinitis patients (40.00%) compared to controls (33.33%). CC genotype was observed to have a significant increased frequency in patients compared to controls while CTand TT genotype frequencies were significantly decreasedin patients compared to controls, increased risk of asthma might be associated with CC genotype, while the genotypes CT and TT are thought to havea protective effect from asthma. Season of mites allergy have major role for disease, the positive Skin Prick test for Dermatophagoidespteronys sinus, (D. p) (46.67%), Dermatophagoides farina (D.f) (70.00%) increased in winter (55.00%) while Glycyphagusdomesticus positive Intradermal skin test (47.67%) increased in autumn. Genetic polymorphism and environmental factors play major role for House dust and Storage Mite mite’s allergy.Keywords: House Dust Mites (HDM), Storage Mites, Serum IL-4, Serum Total IgE, Gene polymorphism IL-4, Allergic Rhinitis and Asthma.